Minor harassments: Ethnic minority youth in the Nordic countries and their perceptions of the police - Haller, Mie Birk (Criminology & criminal justice, 2020)
As different social groups are directly and indirectly confronted with diverse forms of police practices, different sectors of the population accumulate different experiences and respond differently to the police. This study focuses on the everyday experiences of the police among ethnic minority young people in the Nordic countries. The data for the article are based on semi-structured interviews with 121 young people in Sweden, Norway, Finland and Denmark. In these interviews, many of the participants refer to experiences of “minor harassments” - police interactions characterized by low-level reciprocal intimidations and subtle provocations, exhibited in specific forms of body language, attitudes and a range of expressions to convey derogatory views. We argue that “minor harassments” can be viewed as a mode of conflictual communication which is inscribed in everyday involuntary interactions between the police and ethnic minority youth and which, over time, can develop an almost ritualized character. Consequently, minority youth are more likely to hold shared experiences that influence their perceptions of procedural justice, notions of legitimacy and the extent to which they comply with law enforcement representatives.